Functional Magnetic Resonance Urography in Ureteropelvic Junction Obstruction: Proposal for a Pediatric Quantitative Score - Damasio, Maria Beatrice; Sertorio, Fiammetta; Wong, Michela Cing Yu; Campo, Irene; Carlucci, Marcello; Basso, Luca; Anfigeno, Lorenzo; Bodria, Monica; Pistorio, Angela; Piaggio, Giorgio; Ghiggeri, Gian Marco; Mattioli, Girolamo (Frontiers in Pediatrics, 2022)
Background: ureteropelvic junction obstruction (UPJO) is one of the most frequent causes of congenital hydronephrosis. It is essential to distinguish UPJO which needs surgical treatment. fMRU combines high quality morphological details of the kidney and excretory pathways with functional data. Objective: to introduce a new radiological score based on fMRU findings able to differentiate surgical from non-surgical kidneys. Materials and methods: we retrospectively selected patients with hydronephrosis due to UPJO who underwent fMRU (January2009-June2018). A multidisciplinary team identified a list of fMRU morpho-functional predictive variables to be included in the analysis. To evaluate the role of different independent variables in predicting the outcome, a multivariable logistic regression model has been performed; the outcome variable was the surgical intervention. For each predictive variable, Odds Ratio and 95% Confidence Intervals were calculated. The Likelihood Ratio test was used to assess the significance of the variables. Using the regression model, we assigned a numerical value to each predictive variable, rounding up the beta-coefficients. The cut-off value of the total score was obtained from the ROC curve analysis. Results: 192 patients were enrolled, corresponding to 200 pathological kidneys. All of them underwent fMRU; 135 were surgically treated, while 65 underwent ultrasound or MRU follow-up. Predictive variables significantly associated with surgery resulted to be the urographic phase, the presence of abnormal vessels and a baseline antero-posterior pelvic diameter greater than 23 mm. Beta coefficient of the logistic regression model were then converted in scores. The ROC curve of the score showed high sensitivity (84.3%) and specificity (81.3%) with a cut-off > 2.5. Conclusions: We propose a new fMRU score able to identify surgical versus non-surgical kidneys with UPJO.